2020
DOI: 10.1002/ppul.24690
|View full text |Cite
|
Sign up to set email alerts
|

Postinfectious bronchiolitis obliterans masked by misdiagnosis as asthma

Abstract: Objectives Asthma and postinfectious bronchiolitis obliterans (PIBO) have similar clinical findings, and PIBO may be misdiagnosed with asthma. This study aimed to determine the clinical features of PIBO in children and the causes of delay in its diagnosis. Methods We retrospectively evaluated all patients diagnosed with PIBO in four pediatric pulmonology centers between 2007 and 2018. In total, 64 PIBO patients were retrospectively reviewed. We compared the clinical and laboratory differences between PIBO pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
1
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 15 publications
1
9
1
2
Order By: Relevance
“…Some studies suggested that atopy could be associated with PIBO. 17,18,19,20 Similarly, in our study, approximately 20% of our patients had atopy.…”
Section: Discussionsupporting
confidence: 80%
“…Some studies suggested that atopy could be associated with PIBO. 17,18,19,20 Similarly, in our study, approximately 20% of our patients had atopy.…”
Section: Discussionsupporting
confidence: 80%
“…In the current study, we found that although the proportion of children with RMPP pneumonia complicated with in uenza infection was higher than that of non-BO children, multivariate regression analysis found that in uenza infection was not a risk factor for the development of BO after RMPP. It is widely known that adenovirus infection is one of the risk factors for the development of BO in children [20]. In the current study, we did not nd an association between adenovirus co-infection and the development of BO after RMPP, which may be related to the small sample size.…”
Section: Discussioncontrasting
confidence: 78%
“…In the current study, we found that although the proportion of children with RMPP pneumonia complicated with influenza infection was higher than that of non-BO children, multivariate regression analysis found that influenza infection was not a risk factor for the development of BO after RMPP. It is widely known that adenovirus infection is one of the risk factors for the development of BO in children [ 20 ]. In the current study, we did not find an association between adenovirus co-infection and the development of BO after RMPP, which may be related to the small sample size.…”
Section: Discussionmentioning
confidence: 99%